Navigating Marginalization:: Safety and Survival for Low-Income Women in Bangladesh’s Informal Economy - Siddique, Adhina Binte; Turza, Asif Ibney Basit (The Jahangirnagar Review, 2025)
Women of low socioeconomic status in Bangladesh encounter pervasive occupational insecurity, particularly in domestic work, as a result of systemic capitalist exploitation and legislative deficiencies. Despite their significant contributions to the informal economy, they are excluded from the Labour Act of 2006, and the inadequate implementation of the Domestic Workers Protection and Welfare Policy ,2015 further intensifies their discrimination. This study follows a mixed-methods approach, integrating field surveys, observational methods and data analysis to identify the factors leading to their insecurity. The study reveals that domestic workers, who are mostly young, rural migrants, suffer from economic hardship, wage discrimination, job insecurity, and social discrimination, and women are facing higher sexual harassment and vulnerabilities since they have limited legal protections and financial autonomy . The research highlights the need for policy changes, societal awareness and cultural changes to protect the rights of domestic workers and improve financial stability and security.